Effect of different albumin media on the lipid-mobilizing action of sympathicotropic substances in vitro - Lincová, D; Cepelík, J; Cernohorský, M; Elisová, K (Physiologia Bohemoslovaca, 1977)
The authors studied the effect of adrenotropic substances on lipolysis in rat epididymal adipose tissue in albumin medium in vitro. On using albumins of different origin (human, bovine), the pD2 values for catecholamines differed by more than one order, in correlation to the type of albumin used. The isopropylnorsynephrine pD2 values did not differ. The addition of ascorbic acid (100 microng/ml) raised the catecholamine pD2 values and completely equalized the pD2 values found in both media. The pD2 values for the synephrine derivative did not alter. The propranolol pA2 values were not negatively affected by the addition of ascorbic acid. Ascorbic acid also produced a mild increase in the maximum lipid-mobilizing values obtained with any of the given substances in either medium. It was concluded in the discussion that catecholamines are oxidized at different rates in different albumin media and that this oxidation can be inhibited by adding ascorbic acid. Ascorbic acid likewise mildly stimulates the maximum lipid-mobilizing effect. The authors recommend the addition of ascorbic acid to albumin medium as a regular component for the study of adrenergic lipid mobilization.
Keywords: Rats; epididymis; In Vitro Techniques; Epididymis; albuminy; mobilizace lipidů; mužské pohlaví; propranolol; techniky in vitro; krysa rodu Rattus; Albumins; zvířata; Catecholamines; kyselina askorbová; Propranolol; Lipid Mobilization; katecholaminy; Ascorbic Acid; Male; Animals